Collaborative Public Governance in Implementing Indonesia's One Fuel Price Policy: Evidence from Fuel Distribution in Frontier, Outermost, and Disadvantaged Regions - Adam Jamal; Deydeandy Luckymirdajuba Iztighfari (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2026)
Indonesia's One Fuel Price Policy aims to reduce energy disparities by ensuring equal fuel prices in frontier, outermost, and disadvantaged (3T) regions. While the policy has expanded fuel access, limited studies have examined its implementation from an integrated public governance and public management perspective. This study analyzes the collaborative governance structure, policy implementation, and strategic communication supporting the program. A qualitative descriptive approach was employed using secondary data from official regulations, reports, and publications issued by the Downstream Oil and Gas Regulatory Agency (BPH Migas), the Ministry of Energy and Mineral Resources, and Pertamina. The data were analyzed through thematic content analysis. The findings indicate that policy implementation is supported by collaborative governance involving central and local governments, BPH Migas, and Pertamina, resulting in the establishment of 583 fuel distribution points despite significant geographical and logistical challenges. Strategic communication also enhances coordination and public trust throughout implementation. This study demonstrates that integrating collaborative governance, adaptive public management, and strategic communication strengthens policy implementation and provides practical insights for delivering equitable public services in geographically challenging regions.